1994
DOI: 10.5014/ajot.48.4.346
|View full text |Cite
|
Sign up to set email alerts
|

Transition From School to Community Living

Abstract: The transition process by which a student with moderate to severe disabilities is prepared to leave the school setting and enter into employment and community living is legally mandated and includes provisions for occupational therapy and other related services. This transition requires a team approach in which members collaborate to determine objectives with the student and his or her family in the domains of domestic, community, recreational, and vocational living. Assessment and intervention focus on functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Ontario education policy has mandated that support services be provided to enable al1 children with disabilities to attend regular schools and have access to the opportunities and resources that will enable thern to reach their optimum potential (Keeton-Wilson, 1985). In spite of this, research suggests that young adults with physicai disabili ties have di fficulty with the transition from ~h o o l to adult community life (Blum, 199 1;Brollier, Shepherd, & Markiey, 1994;Clark, Mack, & Pennington, 1989;Kekkonen, Saukkonen, Serio, & Kimunen, 1991; Parmenter & Knox, 1991).…”
Section: Rationale For the Research Topicmentioning
confidence: 99%
“…Ontario education policy has mandated that support services be provided to enable al1 children with disabilities to attend regular schools and have access to the opportunities and resources that will enable thern to reach their optimum potential (Keeton-Wilson, 1985). In spite of this, research suggests that young adults with physicai disabili ties have di fficulty with the transition from ~h o o l to adult community life (Blum, 199 1;Brollier, Shepherd, & Markiey, 1994;Clark, Mack, & Pennington, 1989;Kekkonen, Saukkonen, Serio, & Kimunen, 1991; Parmenter & Knox, 1991).…”
Section: Rationale For the Research Topicmentioning
confidence: 99%
“…The student may need information about contraceptive options and alternative means for being sexually intimate. Guidance with foresight is most effective if presented within an empowering framework that emphasizes responsibility, accountability, and selfdetermination (Brollier, Shepherd, & Markley, 1994). Students can be instructed and supported to become their own service coordinator and learn to advocate for needed services.…”
Section: Instructional Accommodationsmentioning
confidence: 99%
“…Others have indicated that the time and inconvenience of having to teach and train the adolescent in a task had a significant negative impact upon their family routine (Brollier, Shepherd, & Markley, 1994).…”
Section: Influence On Independencementioning
confidence: 99%
“…Positive reinforcers and consequences should also be used to facilitate the learning process (Brollier et al, 1994).…”
Section: Skill Developmentmentioning
confidence: 99%
See 1 more Smart Citation